1997
DOI: 10.1109/23.659021
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation response of mobile protons in buried SiO/sub 2/ films

Abstract: We have performed current-voltage, capacitancevoltage and electron-paramagnetic-resonance (EPR) characterization of silicon-on-insulator (SOI) samples, subjected to a wide variety of irradiation and anneal treatments. By comparing transport properties and interfacial reaction mechanisms, we provide evidence for an intrinsic difference in the response of mobile protons in these oxides, depending on whether they are generated by irradiation or by & annealing. A radiation effects study of SO1 buried oxides contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
2
16
1
Order By: Relevance
“…The recent work [15][16][17][18][19][20][21][22][23] shows that annealing in forming gas at temperatures of 500°C or above can introduce a large number (ϳ10 12 cm Ϫ2 ) of fixed and/or mobile positive charges in the oxide. The fixed positive charge has characteristics similar to the oxidation-induced fixed charge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent work [15][16][17][18][19][20][21][22][23] shows that annealing in forming gas at temperatures of 500°C or above can introduce a large number (ϳ10 12 cm Ϫ2 ) of fixed and/or mobile positive charges in the oxide. The fixed positive charge has characteristics similar to the oxidation-induced fixed charge.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile charges are so securely imprisoned in the device that it is proposed that they can be used to form nonvolatile memory devices. 18 Recent work [15][16][17][18][19][20][21][22][23] has improved our understanding in H 2 -induced positive charge generation significantly. The work was mainly carried out in the buried oxide fabricated for silicon-on-insulator ͑SOI͒ devices, although it was shown that mobile charges can also be created in some specially processed and thermally grown oxides.…”
Section: Introductionmentioning
confidence: 99%
“…The device is based on a stacked Si/SiO#3i structure, subjected to an anneal at -1100 "C in an inert ambient. Mobile protons ((&+) can be generated in the dielectric of such structures by subjecting them to a forming-gas anneal at temperatures >400 "C. The protons are found to be stable, even under field and thermal stressing and irradiation, i.e., they do not easily escape the dielectric or trap electrons [6]. These observations have been confirmed by other workers [7].T here are several reports in the literature of mobile protons in Si02, which have been generated electrically or by: irradiation in specific types of SiOz [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies in the literature have shown that protonic memory elements are (1) stable to at least lo6 cycles, with no degradation in window size [lo], (2) tolerant to -1 Mrad(Si0,) unbiased total dose radiation exposure [IO], and (3) resistant to at least 250°C temperature without significant loss of hysteresis [19]. Hence, we conclude that protonic memory elements can potentially serve as the basis for a lowvoltage, radiation-tolerant nonvolatile memory technology.…”
Section: (After Ref [9])mentioning
confidence: 99%
“…To date, the studies of protonic memory elements in the literature have focused on relatively large geometry capacitor and pseudo-MOSFET test structures [9], [10], [15], [19]. When these structures are scaled down to the submicron regime, there is the possibility that the protons may not be as easily confined and controlled as they are in the structures studied to date, e.g., if there are signficant lateral components to the oxide electric fields.…”
Section: Process Integration Issuesmentioning
confidence: 99%